PEMBUATAN PAKAN KONSENTRAT DI KELOMPOK PETERNAK KELINCI MANDIRI DESA NGIJO KECAMATAN KARANGPLOSO KABUPATEN MALANG - Marhaeniyanto, Eko; Trisna Murti, Ariani; Susanti, Sri (PEDULI: Jurnal Ilmiah Pengabdian Pada Masyarakat, 2017)
Production of rabbit can be improved through the availability of cheap feed. The solution offered is the manufacture of concentrated feed based on local ingredients.  The availability of concentrate feed in the association of "Mandiri" rabbit breeders may encourage increased productivity of rabbits. Results of the implementation of Science and Technology for Society (IbM) to increase production, both quantity and quality, enhance partners' understanding and skills, increase sales turnover, improve the peace / health of the community, produce concentrate feed products and published Practical Book of Animal Husbandry "Rabbit-Based Concentrate and Processed Feed Products". Implementation of activities in the form of production of commercial rabbit concentrate feed. Equipment used are chopper machine, penepung machine, oven and pellet printing machine production capacity of 75-100 kg / hour.  IbM Program at Mitra rabbit breeder "Mandiri" produces feed of rabbit concentrate, increase production capacity and efficiency, preparation of SOP and accompaniment implementation, and the establishment of standard sanitation operating procedure.